The evolution of studies in traffic management: a systematic literature review (2007-2018) - Yaduvanshi, Rachna; Bansal, Sanjeev; Kumar, Anita (International Journal of Engineering and Technology, 2019)
The purpose of this paper is to critically review the papers published in the area of traffic management system. The current Traffic conges-tion in our highway networks should be addressed with top most priority. And steps to identify the issues and challenges associated with traffic congestion in our highway networks including National highway, state highways, fast-transit corridors, and traffic hubs shall be analyzed to understand the basic root causes of traffic congestion. The paper aims to critically evaluate the available evidence on the contri-bution of traffic management systems. Design methodologyâ€“ structured literature review approach is adopted to analyze the previously pub-lished papers. Findings â€“ The review concludes that there is a growing body of research that supports the assertion that integrated traffic management system is the solution for the current congestion of traffic situations in major metro cities. The findings also conclude that lim-ited amount of work has been carried out in the field of integrated traffic management system in India.Â Â